The social cohesion in the Syrian society-Theoretical study of the reality of social cohesion in Syrian society during the war on Syria- (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The concept of social cohesion refers to the extent of stability in the level of social construction in terms of the relationship of the individual to his community and his relationship with others and the importance of the study as it deals with one of the subjects that have contributed to the terrorist war in Syria, this led to the weakening  of social structures and aims to identify the reality of the Syrian society in terms of its cohesion or disintegration through a critical study of the reality of the situation in Syria after the terrorist war in which it was perceived. A significant role in its occurrence at all levels of community, family, religious, and media. يشير مفهوم التماسك الاجتماعي إلى مدى الاستقرار على مستوى البناء الاجتماعي لجهة علاقة الفرد بمجتمعه وعلاقته مع الآخرين، وتأتي أهمية الدراسة كونها تتناول إحدى الموضوعات التي قد أسهمت الحرب الإرهابية على سوريا في إحداث خلخلة كبيرة على مستويات الحوامل الاجتماعية فيها، ويهدف للتعرف إلى حال واقع المجتمع السوري من حيث تماسك بنائه أو تفككه من خلال دراسة نظرية نقدية لواقع الحال في سوريا بعد أن عصفت الحرب الإرهابية بها، وكانت أبرز النتائج تؤكد على وجود خلخلة واضحة في البناء الاجتماعي للمجتمع السوري، لعبت أسباب عديدة وأبرزها الحرب دوراً كبيراً في حدوثه على كافة المستويات المجتمعية سواءً على صعيد الأسرة أو المؤسسات الدينية أو الإعلامية.